Parameter und Indizes zur Bewertung des Naturraumpotentials. Beispiele aus Nordhessen - Stäblein, Gerhard (ERDKUNDE, 1989)
Landscape and natural environment are basic paradigms in geographical approaches. In the actual applied aspects of environmental management it is important to develop practical evaluation methods of the natural potential in an area and the impact of different land uses.A system of potentials for different land uses is discussed. The negative impact of a landscape can be calculated in a first step by a land use balance. The diversification of natural phenomena in a landscape section can be determined by a complex index giving a qualitative value as to possible leisure time activities. The geoecological potential and the stability of the natural landscape system’s balance can be judged by determining several properties of the natural divisions, e.g. the soil conditions in an areal section determined by filter quality, erosion disposition, permeability to water - The different methodological approaches are presented here by landscape sections of northern Hesse (Central Europe) as examples.